PERLINDUNGAN HUKUM TERHADAP ANAK DALAM PROSES PERCERAIAN ORANG TUA PADA PERKARA NOMOR 404/PDT.G/2024/PA BB (STUDI KASUS DI PENGADILAN AGAMA BAUBAU KELAS II) - La Ode Muhammad, Muskur; Moh, Rizqi (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
Indonesia regulates marriage through Law Number 16 of 2019, which stipulates the conditions, rights, and obligations of husband and wife to create a harmonious family. However, domestic conflict often leads to divorce, which has a negative impact, especially for children who become victims. This study aims to understand and explain the facts that occur and the application of norms in practice. In the context of child custody after divorce, it can also determine the efforts that can be taken if the decision is not implemented. The type of research applied in this study is a qualitative method, namely empirical legal research. This research focuses on an in-depth analysis of legal documents, as well as conducting observations and interviews with subjects in the field. The judge carefully considered granting custody to the plaintiff, namely the mother, because the children are still in a state of mumayyiz and unable to care for themselves. The plaintiff is required to provide access to the defendant to meet the children, and preventing meetings can be grounds for the court to revoke custody. If the children's rights are not fulfilled, there are two efforts that can be taken: execution and detention of the divorce certificate by the court.